ANALISIS TINGKAT RISIKO BANK PADA BANK PEMBANGUNAN DAERAH DI INDONESIA - Anggaredho, Panji Patra; Margie, Lyandra Aisyah; Sari, Imelda; Marginingsih, Ratnawaty; Sibarani, Bintang Berliana (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This study aims to analyze the level of risk in Regional Development Banks in Indonesia. This study intends to examine and map the risk of banks in BPD in Indonesia. In this analysis, the level of bank risk is measured using Z-Score (Z score). The data used in this study are panel data of observations from 26 Regional Development Banks in Indonesia over the past 20 years (2001-2021) which are divided into four clusters, namely the Sumatra Cluster, the Java, Bali and Nusa Tenggara Cluster, the Kalimantan Cluster and the Sulawesi and Eastern Indonesia Cluster. The data analysis technique used is using the Anova Test with the help of the SPSS program. The results of this study concluded that: 1) Bank risk in BPD Sumatra region has the same level of stability as BPD in Java, Bali & Nusa Tenggara. 2) Bank risk in BPD in Kalimantan region has the same level of stability as BPD in Sulawesi & Eastern Indonesia region.